ANALISIS PERLAKUAN AKUNTANSI ASET TETAP MENURUT PSAK NO.16 (REVISI 2011) DI RSU PANCARAN KASIH MANADO - Sadondang, Paulina Amanda; Sondakh, Jullie J; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2015)
Fixed assets has an important role to prop up the course of company operational activities, therefore the right policy of the fixed assets management is needed to maximize the role of the fixed assets. On this situation, accounting policy of the fixed assets as an information tools about fixed assets is really needed by the decision maker.RSU Pancaran Kasih Manado is an institution of Medika GMIM foundation that provided service like a public health facilities. Land, building, vehicle, medicalÂ and non medical tools are the fixed assets that owned by company and very important to propped the course of company operational activities.This research aim for analyze the accounting treatment for fixed assets at RSU Pancaran Kasih Manado, whether it has in accordance with the statement of financial accounting standard No. 16 (revised 2011) about fixed assets..The method of research used is descriptive analyze method with the purpose to give an illustration or description about a situation in an objective manner. To compile data necessary, writer used the technique of gathering data like an interview and documentation. The kind of data that used are primary data and secondary data.From the result of research can be deduced that in operated accounting activity, the company has following provisions on PSAK No. 16 (Revised 2011) about fixed assets. On the application, the company distinguish the kind of fixed assets and the achievement method, that is cash purchase, construction, or donation, shrinking the fixed assets used straight line method, halt the fixed assets that is not used, removed the fixed assets from own list and take it off by abrogation and annihilation. But on the disclosure, the company not apply the accounting treatment of fixed assets altogether like that PSAK No. 16 (Revised 2011).